A SYNTACTIC ANALYSIS OF PASSIVE CONSTRUCTIONS IN AMANUBAN DIALECT OF UAB METO (DAWAN) IN OE'O VILLAGE, OENINO SUBDISTRICT, TIMOR TENGAH SELATAN DISTRICT - Elis Adriana Tenis; Rudolof J. Isu; Yanrini M. Anabokay (Media Inovasi Pendidikan dan Publikasi, 2026)
This study provides a syntactic analysis of passive constructions in the Amanuban dialect of Uab Meto, an Austronesian language spoken in East Nusa Tenggara, Indonesia. Using a qualitative descriptive method, data were collected from four native speakers through elicitation tasks involving active–passive pair transformations. The analysis reveals that passive voice in Amanuban Uab Meto is encoded exclusively through word-order rearrangement without any morphological marking on the verb. Active clauses follow an SVO order, while passive clauses exhibit a rigid S (patient) – O (agent) – V pattern. The agent is syntactically obligatory, and tense/aspect features are hosted on the agent phrase rather than on the verb. Ditransitive constructions allow promotion of the direct object to subject. These findings indicate that the passive in this dialect is a purely syntactic phenomenon driven by constituent reordering. The study contributes to the typology of voice systems in Austronesian languages and provides documentation of an underdescribed dialect.